Fostering green investments and tackling climate-related financial risks: Which role for macroprudential policies? - Paola D'Orazio; Lilit Popoyan (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
While there is a growing debate among researchers and practitioners on the possible role of central banks and financial regulators in supporting a smooth transition to a low-carbon economy, the information on which macroprudential instruments could be used for reaching the "green structural change" is still quite limited. Moreover, the achievement of climate goals is still affected by the so-called "green finance gap". The paper addresses these issues by proposing a critical review of existing and novel prudential approaches to incentivizing the decarbonization of banks' balance sheets and align finance with sustainable growth and development objectives. The analysis carried out in the paper allows understanding under which conditions macroprudential policy could tackle climate change and promote green lending, while containing climate-related financial risks. – – Während unter Forschern und Praktikern eine zunehmende Debatte über die mögliche Rolle von Zentralbanken und Finanzaufsichtsbehörden bei der Unterstützung eines reibungslosen Übergangs zu einer kohlenstoffarmen Wirtschaft stattfindet, sind die Informationen darüber, welche makroprudentiellen Instrumente zur Erreichung des "grünen Strukturwandels" eingesetzt werden könnten, noch recht begrenzt. Darüber hinaus wird die Erreichung der Klimaziele noch durch die so genannte "green finance gap" beeinflusst. Das Papier befasst sich mit diesen Fragen, indem es eine kritische Überprüfung bestehender und neuartiger aufsichtsrechtlicher Ansätze vorschlägt, um Anreize für die Dekarbonisierung der Bankbilanzen zu schaffen und die Finanzierung an den Zielen für nachhaltiges Wachstum und Entwicklung auszurichten. Die in dem Papier durchgeführte Analyse ermöglicht es zu verstehen, unter welchen Bedingungen die makroprudentäre Politik den Klimawandel bekämpfen und die umweltfreundliche Kreditvergabe fördern könnte, während sie gleichzeitig klimabedingte finanzielle Risiken begrenzt.
Keywords: E50; E52; G28; Q50; Q58; 330; climate change; climate finance gap; banking regulation; macroprudential policy; central banking; climate-finance risk